Folklore as a Decolonial Tool: Examining Isabelo de los Reyes’s El Folk-Lore Filipino - Presto, Athena Charanne R.; Viceral, Emmanuel Reed Horton B. (BANWAAN: The Philippine Journal of Folklore, 2025)
We employ reflexive content analysis to examine Isabelo de los Reyes’s El Folk-Lore Filipino . Written in Spanish and rooted in the folklore of Ilocandia, de los Reyes’s seminal work counters the colonial assertion that a sophisticated Philippine civilization did not exist prior to Spanish colonization. This article’s analysis, informed by the authors’ positionality as Ilocanos born and raised in Ilocos Sur (first author) and Ilocos Norte (second author), attempts to situate Ilocano folklore within its contemporary cultural framework. We argue that folklore, as seen in de los Reyes’s work, acts as a subversive force against colonial narratives by accomplishing three key objectives: umuna (first), it reveals how Ilocano folklore is a dynamic knowledge system that integrates and recontextualizes colonial influences. Maikadua (second), it challenges the colonial dichotomy that juxtaposes perceived barbaric traditional beliefs with so-called civilized modernity. Maikatlo (third), by comparing Filipino superstitions with those of their colonizers, folklore demonstrates the universality of such beliefs while dispelling notions of primitivism surrounding Filipino cultural practices. This analysis aims to showcase El Folk-Lore Filipino as a pivotal text in decolonizing Philippine history, culture, and society through the text’s contribution in correcting a distorted view of Ilocano and broader Filipino identity. Keywords: decolonization, decolonial narratives, content analysis, sociology of knowledge, nationalism, Isabelo de los Reyes